2002
DOI: 10.1038/sj.leu.2402404
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide induces the apoptosis of human BCR-ABL-positive myeloid leukemia cells: evidence for the chelation of intracellular iron

Abstract: Anti-leukemia activity of human macrophages involves the generation of nitric oxide (NO) derivatives. However, leukemic transformation may involve mechanisms that rescue cells from NO-mediated apoptosis. In the present work, we analyzed the effects of exogenous NO on the proliferation of BCR-ABL

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 41 publications
0
11
0
1
Order By: Relevance
“…Thus, the addition of SNP or other iron compounds efficiently protected various tumor cells from NO-mediated growth inhibition and apoptosis (7,8). Furthermore, SNP rescued hypoxia-induced death of C6 glioma cells via the iron-dependent activation of the Na ϩ -Ca 2ϩ exchanger (1).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the addition of SNP or other iron compounds efficiently protected various tumor cells from NO-mediated growth inhibition and apoptosis (7,8). Furthermore, SNP rescued hypoxia-induced death of C6 glioma cells via the iron-dependent activation of the Na ϩ -Ca 2ϩ exchanger (1).…”
Section: Discussionmentioning
confidence: 99%
“…Nitric oxide (NO) has been shown to be involved in apoptosis signaling pathway in many diseases, such as anemia of chronic diseases [7], aplastic anemia [8] and leukemia [9]. NO is synthesized from L -arginine by NO synthase (NOS), which exists in three isoforms, namely, neuronal NOS, inducible NOS (iNOS) and endothelial NOS [10,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…However, at high concentrations, nitroxide radicals may be formed and cause damage to the local environment (Morehouse et al, 1987). Other clinical uses for DFX include cancer therapies (Becton and Bryles, 1988;Lee and Wurster, 1995;Ferry-Dumazet et al, 2002;Buss et al, 2003;Dayani et al, 2004;Brard et al, 2006). Kim et al (2002) and Choi et al (2003) have shown that p38 MAP kinase plays an important role in the DFX-mediated death of HL-60 cells, and that downregulation of the p38 kinase pathway by the cAMP response element-binding protein protects HL-60 cells from DFX-induced apoptosis.…”
Section: Introductionmentioning
confidence: 99%